TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK): THE READINESS OF HIGHER EDUCATION EDUCATORS FACING THE DIGITAL TRANSFORMATION IN TEACHING AND LEARNING - Atri Nadia Astarina; Meita Lukitawati Sujatna; Heri Heryono (PROJECT (Professional Journal of English Education), 2024)
Implementing digital learning systems in Higher Education presents a challenge for educators as they strive to incorporate technology in the educational process in a manner that is active, interactive, and conducive to achieving student learning objectives. The goal of this study is to outline the capability and preparedness of instructors in utilizing digital learning, focusing on the Technological Pedagogical Content Knowledge (TPACK) framework established by Mishra & Koehler (2006). The study, which used a qualitative approach, involved 25 lecturers from the Faculty of Cultural Sciences of a private university as participants. The data was gathered by distributing surveys using Google Forms on the internet. The collected data were then processed and analysed. The output of this research is expected to be an additional reference for TPACK studies at the Higher Education level which can also be an input for the development of lecturer performance in an institution, especially in increasing lecturer competence in digital learning.